Employee Payroll Accounting Application Using Extreme ProgrammingDevelopment Method - Ramadhani, Nafi; Hidayatulloh, Syarif (JURNAL TEKNIK KOMPUTER AMIK BSI, 2025)
Technology allows company structures to become more effectiveand efficient for payroll system applications, as almost all parts ofthe company have adopted this technology. One such company, PT.Langgeng Engineering Tehnik Indonesia, which produces and sellsspare parts, has an HR department responsible for managingextensive employee data, including payroll data. The process iscurrently done manually with the help of Microsoft Excel,requiring a high level of accuracy and being very prone to errors.The most significant issue is certainly payroll management, as itrelates to the company's finances and employee welfare. To reducethe risk of errors in managing this data, particularly payroll, thisresearch aims to contribute by creating a payroll applicationdesigned to facilitate management in processing and disbursingsalaries to every employee working in the company, while alsominimizing the risk of errors in management. The application isbuilt using the Extreme Programming method, which offersadvantages in terms of rapid development, efficiency, adaptability,and flexibility. This application is developed as a desktop-basedsolution using Java programming language, as its users are limitedand it is intended for internal company use. The application istested using Black Box testing, a technique that evaluates thefunctionality without considering the internal structure ofcomponents or systems. The testing is conducted with eightscenarios, and all tests yield valid results.
Keywords: Payroll; Accountancy; Extreme Programming; Employee